Pengaruh Kekerasan Verbal Orangtua terhadap Konsep Diri Remaja - Hamiyati; Awal, Rahmatia Narita; Nugraheni, Prastiti Laras (Journal of Research and Measurement in Psychology: JPPP, 2022)
This study aims to analyze the effect of parental verbal abuse on adolescents self-concept. The approach used in this study is quantitative associative with a survey method using questionnaire to collect the data. The population in this study was high school students of SMA Negeri 1 Leuwiliang Kabupaten Bogor, with a total sample of 103 respondents selected with the purposive sampling technique. This study uses tests of normality, linearity, and hypotheses as a pre-requisite test. Based on data result, it is known that majority sample are categorized as low level of parental verbal abuse (69,9%) and the adolescents self concept received by the majority sample are belong to middle category (53,4%). Data calculation which used IBM SPSS Statistics 25 shows that parental verbal abuse has a negative and significant effect on adolescents self concept (P-Value = 0.000 < 0.050. This study shows that the higher parental verbal abuse level, the lower adolescents self-concept, . The coefficient of determination obtained is 27,4%, which means that parental verbal abuse affect on adolescents self-concept by 27,4% and the other 72,6% is influenced by other factors not examined in this study.